Synthesis of layered hydroxides using controlled ammonia vapor diffusion - Du, Y; O'Hare, D (2008)
Layered hydroxides Co(OH)1.65Br0.35·0.5H2O (1), Co(OH)1.60(DDS)0.36Cl0.04·2.1H2O (2), Mg2Al(OH)6NO3·3H2O (3) and Mg(OH)2 (4) with unique morphologies have been synthesized by low temperature, controlled ammonia vapor diffusion. The materials were characterized by X-ray powder diffraction (XRD), field emission scanning microscope (FESEM) and SQUID magnetometry. Crystallites of (1) and (4) grow as thin films perpendicular to the air/water interface, while crystals of (2) and (3) share an unusual coral-like morphology. The magnetic data is consistent with a 3D ferrimagnet ground state at low temperature for both (1) and (2). The saturation magnetization (MSAT) at 5 K is observed to be 0.88 and 0.59 μB for (1) and (2), respectively. These values are consistent with a model containing two antiferromagnetically coupled magnetic sublattices, one comprising of octahedral cobalt atoms and one comprising tetrahedral cobalt atoms. © 2007 Elsevier Ltd. All rights reserved.